Biomass production of coppiced grey alder and the effect of fertilization - Hytönen, Jyrki; Saarsalmi, Anna (Silva Fennica, 2015)
We studied biomass production of two naturally originated grey alder ( (L.) Moench) stands having a mixture of birch and willow located in central Finland. One of the stands was growing on a peatland site (Muhos) and the other on a mineral soil site (Juuka). The stands were clear-cut and fertilization experiments were laid out with several treatments. At Muhos, the treatments included nitrogen fertilisation with different amounts of wood ash and an unfertilized control. At Juuka, the treatments included nitrogen fertilisation either with ash or with PK, and ash and PK treatments alone and an unfertilized control. The sprouts at Muhos were grown for 17 years and at Juuka for 20 years. At Juuka the stand was clear-cut second time at the age of 20 years and grown for 8 years. The stands were measured several times and foliar samples were taken twice during the study period. Clear-cutting increased stem number manifold. The stand density of new coppiced forests after the clear-cutting decreased from 67â000â89â000 stems ha at the age of 3â6 years to 10â000â12â000 stems ha at the age of 17â20 years. On neither site fertilization affected biomass production of alders during the study period. Leafless above-ground biomass was 52â57 Mg ha after 17â20 years. Mean annual leafless above-ground biomass production (MAI) increased with increase of rotation time. At the age of 17â20 years the MAI was 2.8â3.0 Mg ha a. At Muhos, ash increased foliar P and Ca concentrations, but decreased those of Mn.Alnus incanaâ1â1â1â1